Environmental assessment of the Canada goose use reduction program proposed for east-central Wisconsin. - Wisconsin. Dept. of Natural Resources.; U.S. Fish and Wildlife Service. ([Madison, Wis.?] : U.S. Fish and Wildlife Service and the Wisconsin Dept. of Natural Resources, 1976)
Two U.S. Fish and Wildlife Service pamphlets, "Horicon National Wildlife Refuge, Wisconsin" and "Birds, Horicon National Wildlife Refuge" stapled in as appendices. Includes bibliographical references (p. 58). Mode of access: Internet.